Analysis of Market Competitiveness of Container Railway Transportation - Pingbiao Zheng; Shiqi Quan; Wenjun Chu (Journal of Advanced Transportation)
With the personalized and diversified development of customer demand in the freight market, road transportation has become a main competitor of railway transportation in container transportation due to its high flexibility, convenience, and low prices. Based on the generalized cost and logit model, this paper constructs a container railway goods transport market competitiveness model including four indicators of economy, timeliness, environmental protection, and safety. Take 20 ft container transportation as an example, the impact of changes in railway goods charge and railway travelling speed on the competitiveness of the railway goods transport market is analysed. Some realistic suggestions, including optimizing the railway tariff system, increasing the travelling speed of railway, innovating container intermodal products, and making full use of policy-oriented advantages are concluded.